‘Damn, Norway’. Place Branding as a Function of Local Campaigns and Global Actors: English - Robinson, Jessica Yarin (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
Social media platforms are believed to offer new opportunities for place branding practitioners, but also change who participates in the process. This paper investigates the role of global networks in shaping the image of a place, focusing on foreign users. This audience was once considered the target of place branding campaigns, but now have the ability to be active participants. Drawing on a year-long data collection of nearly 6-million tweets about Norway, the study uses quantitative and qualitative methods to understand the spatial and temporal dimensions of place branding online. The findings suggest that international users take a leading role in shaping the conversation, especially in response to local news events. While foreigners largely reinforce the official place brand, they also deploy the brand as a political symbol. These findings are discussed in relation to both the practitioner and critical literature on place branding.